Development of Macromedia Flash-Based Learning Media On Water Cycle Material for Grade V Elementary Schools - Wida Oktavia Andayani; Dhian Dwi Nur Wenda; Kukuh Andri AKa (Universitas Nusantara PGRI Kediri, 2026)
This research has a background problem in SDN Wates, Kediri Regency. In grade V teachers are only fixated on lecture methods and conventional learning media, namely textbooks that only contain writing to explain the material, the material in the book is also limited. Textbooks that have a single purpose do not involve students' activeness directly. The less consistent font form in the textbook makes students more bored and there is no variation such as less interesting images. The solution to this research is that researchers develop interactive learning media based on macromedia flash in science subjects for grade V Elementary School students. The purpose of this study is to determine the validity, practicality, and effectiveness of Macromedia Flash-Based Learning Media for grade V Elementary School students. The model used in this research and development is the ADDIE model consisting of five stages, namely: 1) analysis, 2) design, 3) development, 4) implementation, and 5) evaluation. The results of the validation study by media experts are 82% and material experts 88% with an average of 85% very valid. Practicality obtained from teacher responses was 92% and student responses were 94%, with an average of 93% being very practical. Media effectiveness was 87% on a broad scale and 85% on a limited scale with an average of 86%, meaning it met the Minimum Competency Standard (KKM) and was effective to use.